THE RELATIONSHIP BETWEEN STUDENTS’ SELF-EFFICACY AND LEARNING OUTCOMES IN ENGLISH LANGUAGE LEARNING - Muchtar, Rezki Nurhidayah; G, Hasriani; Sally, Fauzan Hari Sudding (Universitas Negeri Makassar, 2025)
This research seeks to recognize the causality between students' self-efficacy and their learning outcomes in English language learning. The method used was quantitative with a sample of 32 students of class VIII'4 which was obtained through a random sampling method. In obtaining the data, the researchers used questionnaires and documentation as research instruments. The findings from the data analysis indicated that the connection between students' self-efficacy and their learning outcomes had a very strong relationship. It was proven by the F value of self-efficacy and students’ learning outcomes which was 0.001 < 0.05. Therefore, H0 is dismissed, and Ha is affirmed. It was concluded that the association between students’ self-efficacy and students’ learning outcomes in English language learning in class VIII'4 SMP Negeri 2 Sungguminasa is a very strong relationship.